Learning Through "ARBOR Exhibition": Utilizing the Arboretum of Universitas Padjadjaran for Innovative Learning in Higher Education - Rohmatullayaly, Eneng Nunuz; Irawan, Budi; Madihah, Madihah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
The Arboretum Universitas Padjadjaran, as a living collection or museum, is a valuable educational resource for science education, promoting hands-on activities, student-centered learning, and rich social interaction. Aligned with the Outcome-Based Education (OBE) curriculum, the arboretum can be integrated to develop learning innovation, particularly in the “Digitalization of Biological Objects,” which leads to bio-curators’ competencies. Visual arts can be an excellent strategy for learning science, as it combines systematic work with creative thinking. Through this approach, the students can apply theory to real-life experiences. This study aimed to utilize the Arboretum Universitas Padjadjaran to implement innovative strategies for effective learning in higher education through exhibitions. This study used the Research and Development (R&D) method. “ARBOR: The Art and Beauty of Universitas Padjadjaran’s Pollinator” is a photography talk show and exhibition providing information about pollinators, food plants, and host plants in the arboretum and surrounding campus. A total of 135 curated photographs were exhibited digitally. During the exhibition, the students guided over 250 visitors on pollinators and their role in the ecosystem. Our result shows that project-based learning, such as “ARBOR” exhibitions, increased awareness regarding biodiversity and environmental issues and enhanced the students’ leadership, communication, creative thinking, innovation, and collaboration skills, demonstrating the inspiring potential projects in higher education.